Proton Beam Therapy for Children With Neuroblastoma: Experiences From the Prospective KiProReg Registry - Jazmati, Danny; Butzer, Sarina; Hero, Barbara; Ahmad Khalil, Dalia; Merta, Julien; Bäumer, Christian; Plum, Gina; Fuchs, Jörg; Koerber, Friederike; Steinmeier, Theresa; Peters, Sarah; Doyen, Jerome; et al. (Frontiers in Oncology, 2021)
Objective Radiotherapy (RT) is an integral part of the interdisciplinary treatment of patients with high-risk neuroblastoma (NB). With the continuous improvements of outcome, the interest in local treatment strategies that reduce treatment-related side effects while achieving optimal oncological results is growing. Proton beam therapy (PBT) represents a promising alternative to conventional photon irradiation with regard to the reduction of treatment burden. Method Retrospective analysis of children with high or intermediate risk NB receiving PBT of the primary tumor site during first-line therapy between 2015 and 2020 was performed. Data from the prospective in-house registry Standard Protonentherapie WPE – Kinder- (KiProReg) with respect to tumor control and treatment toxicity were analyzed. Adverse events were classified according to CTCAE Version 4 (V4.0) before, during, and after PBT. Results In total, 44 patients (24 male, 20 female) with high (n = 39) or intermediate risk NB (n = 5) were included in the analysis. Median age was 3.4 years (range, 1.4–9.9 years). PBT doses ranged from 21.0 to 39.6 Gray (Gy) (median 36.0 Gy). Five patients received PBT to the MIBG-avid residual at the primary tumor site at time of PBT according to the NB-2004 protocol. In 39 patients radiation was given to the pre-operative tumor bed with or without an additional boost in case of residual tumor. After a median follow-up (FU) of 27.6 months, eight patients developed progression, either local recurrence (n = 1) or distant metastases (n = 7). Four patients died due to tumor progression. At three years, the estimated local control, distant metastatic free survival, progression free survival, and overall survival was 97.7, 84.1, 81.8, and 90.9%, respectively. During radiation, seven patients experienced higher-grade (CTCAE ≥ °3) hematologic toxicity. No other higher grade acute toxicity occurred. After PBT, one patient developed transient myelitis while receiving immunotherapy. No higher grade long-term toxicity was observed up to date. Conclusion PBT was a well tolerated and effective local treatment in children with high and intermediate risk NB. The role of RT in an intensive multidisciplinary treatment regimen remains to be studied in the future in order to better define timing, doses, target volumes, and general need for RT in a particularly sensitive cohort of patients.